Comparison between Vortex-In-Cell and Vortex Particle Methods on Two-Dimensional Problem - Canh, C X; Zuhal, L R; Muhammad, H (AVIA, 2021)
This research is concerned with the two-dimensional vortex method (VM) solvers. We develop and investigate the performance of the Vortex-In-Cell (VIC) and Vortex Particle Method (VPM) which are well known as the VM’s family members. The advantage of these both methods are that we can accelerate velocity computation procedure, an N-body problem in numerical methods, by using Fast Fourier Transform (FFT) and Fast Multipole Method (FMM), respectively. In addition, the viscous calculation process in VPM can be accelerated by using a scheme of Nearest Neighbor Particle Searching (NNPS) algorithms. Moreover, the no-through boundary condition treatment issue can be easily handled by using an immersed boundary condition for both methods. The accuracy and numerical cost of both numerical methods will be examined by simulating flow over an Impulsively Started Circular Cylinder and comparisons